The Influence of Work Environment, Work Motivation, and Compensation on Job Satisfaction and Its Impact on Employee Turnover PNM Mekaar in West Java - Tengku Ariffadillah; Siti Safaria (PT FORMOSA CENDEKIA GLOBAL, 2023)
The desire to switch jobs (Turnover intention) in employees can be affected by few factors including the work environment, work motivation and compensation received by employees. The research aim to determine the effect of work environment, motivation and compensation on PNM employee turnover in West Java province. quantitative analysis. work motivation and compensation affect job satisfaction while work environment not affecting job satisfaction while work motivation has an impact on surgical turnover with work environment, compensation and job satisfaction have no impact on turnover